Ecological Drivers of Invasive Lionfish (Pterois volitans and Pterois miles) Distribution Across Mesophotic Reefs in Bermuda - Goodbody-Gringley, Gretchen; Eddy, Corey; Pitt, Joanna Maria; Chequer, Alex D.; Smith, Struan Robertson (Frontiers in Marine Science, 2019)
Invasive lionfish (Pterois volitans and P. miles) are now ubiquitous throughout the Caribbean and Western Atlantic on shallow and deep reefs. Recent surveys in Bermuda have revealed dense aggregations of lionfish on mesophotic reefs (60 m depth), yet these densities are not pervasive across reefs at this depth. Using diver-led visual surveys of mesophotic reef sites, this study examines how variations in potential ecological drivers may affect lionfish distribution. Significant correlations of lionfish densities were found with prey fish density and prey fish biomass, where sites with higher abundances of prey fishes have greater densities of lionfish. Furthermore, higher densities of lionfish also correlated significantly with higher juvenile Paranthias furcifer biomass, a preferred prey type for lionfish. Prey fish diversity, on the other hand, was not related to lionfish density, nor did prey fish community composition differ in a way that reflected lionfish distributions. The influence of seawater temperature was found to have the strongest effect on lionfish distribution, where higher lionfish densities were found at sites with lower bottom temperature. However, temperature co-varied with prey fish density, prey fish biomass, and P. furcifer biomass, implying that physical parameters of the environment (i.e. temperature) likely influence ecological parameters (i.e. prey fish abundance), contributing to the structuring of lionfish distributions. We suggest, therefore, that cold-water upwelling currents may be fueling the food chain in certain locations, resulting in high abundances of prey fishes and thus lionfish. Understanding the factors that influence lionfish distributions will ultimately increase the efficacy of management strategies, which, as the data presented here suggest, must incorporate mesophotic lionfish populations.